Analysis of various soliton pulsation spectro-temporal dynamics in anomalous dispersion fiber laser. (April 2022) - Han, Ying; Gao, Bo; Wu, Ge; Huo, Jiayu; Chen, Bingkun; Li, Yingying; Guo, Yubin; Liu, Lie
Highlights: Soliton pulsation with time shift caused by soliton explosion. Creeping vibrating soliton molecules. Soliton pulsation with obvious Kelly sideband. Soliton pulsation with soliton splitting. Abstract: In this paper, we studied the effects of the output ratio and small-signal gain on soliton pulsation by modeling the anomalous dispersion carbon nanotube mode-locked fiber laser. Under different parameters, in addition to the conventional soliton pulsation, we also observed the soliton pulsation with obvious Kelly sideband and the soliton pulsation with soliton splitting. And we found the explosive-like soliton pulsation, which exhibits the time shift caused by soliton explosion. Specially, we observed the novel creeping vibrating soliton molecules that has creeping behavior in time-domain but vibrating behavior in spectral evolution. These findings can shed new insights into the soliton complex nonlinear behavior in dissipative systems.